PENGARUH KOMPETENSI, AKUNTABILITAS DAN PROFESIONALISME TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK DI BALI - Ni Made Widya Pradnya Dewi (Hita Akuntansi dan Keuangan, 2022)
This research aims to examine and analyze the effect of Competence, Accountability, Professionalism on the quality of audits at Public Accounting Firms in Bali. The population in this research were all auditors working in Public Accounting Firms in Bali with a total of 108 auditors at 15 KAPs in Bali with a sample of 85 auditors. The data collection technique in this research used a questionnaire. The method of determining the sample uses the purposive sampling method, namely auditors who have at least 1 year of work experience as this data processing method.